She started it - Gilbert, Sian (New York : William Morrow, 2023)
"For fans of Lucy Foley and Liane Moriarty, She Started It is a hot, twisty summer thriller about a group of young women whose Caribbean bachelorette party takes a sinister turn. It's Lord of the Flies meets And Then There Were None...but with Instagram and too much prosecco" Provided by the publisher
Keywords: Bachelorette parties -- Fiction; Female friendship -- Fiction; Secrecy -- Fiction; Summer -- Fiction; Bahamas -- Fiction; Thrillers (Fiction)